New Tools for the Refinement of Sediment Age, Provenance and Routing - Zutterkirch, Isabel Christin (Curtin University, 2024)
Sediments are a valuable archive of the Earth’s geological history. Deciphering this archive can provide insights into past environments, geography and improve correlation and interpretation of the geological record. This work addressed biases in approaches to the most common sediment provenance tool (detrital zircon geochronology), explored sediment recycling through an integrated mineral fingerprinting approach involving zircon U-Pb geochronology and K-feldspar Pb-isotopes, and investigated the complexities of dating fine-grained sedimentary rocks, using the Rb-Sr system.